GUS Histochemical Assay: A Rapid Way to Screen Striped Stem Borer (chilo suppressalis) Resistant Transgenic Rice with a cry1Ab Gene from Bt (Bacillus thuringiensis) - WU Gang; CUI Hai-rui; SHU Qing-yao; YE Gong-yin; XIA Ying-wu (浙江大学学报. 农业与生命科学版)
The time-consuming in vitro bioassay is the frequently used method to screen insect resistant transgenic rice and often remains a tedious task for us. Here we reported the resistance of Bt transgenic rice to striped stem borer by means of field natural infestation and in vitro bioassay. We found that there was a significant correlation between the number of GUS positive plants and the number of insect resistant plants, thus GUS histochemical assay could be used as a rapid and convenient method to screen insect resistant plants.